The Reverse TAL-family of Rules for Bankruptcy Problems - René van den Brink; Juan D. Moreno-Ternero (Tinbergen Institute, 2016)
This paper analyzes a family of rules for bankruptcy problems that generalizes the so-called reverse Talmud rule and encompasses both the constrained equal-awards rule and the constrained equal-losses rule. The family, introduced by van den Brink et al., [Characterization of the reverse Talmud bankruptcy rule by exemption and exclusion properties, European Journal of Operational Research 228 (2013), 413-417], is a counterpart to the so-called TAL-family of rules, introduced and studied by Moreno-Ternero and Villar [The TAL-family of rules for bankruptcy problems, Social Choice and Welfare 27 (2006) 231-249], and it is included within the so-called CIC-family of rules introduced by Thomson [Two families of rules for the adjudication of conflicting claims, Social Choice and Welfare 31 (2008) 667-692]. We provide a systematic study of the structural properties of the rules within the family, as well as its connections with the existing related literature.
Keywords: D63; 330; Bankruptcy problems; Reverse TAL-family; Reverse Talmud rule; Equal awards; Equal losses